Game on: exploring Qatar’s esports development through the lens of vision 2030 - Ahmed Chaib (22673951) (2025)
This paper examines the development and growth of esports in Qatar within the global context of competitive gaming’s rise. It provides an overview of Qatar’s strategic interest in esports as part of its National Vision 2030 economic diversification by drawing on current literature and industry reports on the Qatari and MENA esports ecosystem. This rapid communication article highlights Qatar’s burgeoning esports market and the key drivers, such as government support, institutional initiatives, major tournaments, and educational programs. Discussion of these findings reveals significant opportunities (e.g. youth engagement, digital economy expansion) as well as challenges (nascent local industry, regional competition). The paper concludes with implications for Qatar’s esports ecosystem and offers actionable recommendations for stakeholders (policy makers, investors, educational institutions, and teams) to foster sustainable growth, leveraging Qatar’s strengths in infrastructure and vision for innovation. Other Information Published in: Managing Sport and Leisure License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/23750472.2025.2578259